The Model of Performance: Building Work Discipline and Organization Culture - Peni Cahyati; Nazifah Husainah; Mauritz Sibarani; April Gunawan Malau; Nandan Limakrisna (Dinasti Publisher, 2024)
This study explores the interrelationships between work discipline, organizational culture, and employee performance within organizations. Drawing on a comprehensive review of existing literature and empirical data collected from various industries, the research highlights how a robust organizational culture fosters work discipline, which in turn enhances overall performance. The findings indicate that organizations with a strong, supportive culture are more likely to instill a sense of discipline among employees, leading to increased productivity, decreased absenteeism, and higher employee engagement. Furthermore, the paper identifies key cultural characteristics that promote discipline and suggests practical strategies for leaders to cultivate an environment that aligns with organizational goals. Ultimately, this research underscores the critical role of organizational culture in driving performance and provides a framework for future studies to explore the nuances of these dynamics.